Kewenangan Memutus Sengketa Lembaga di Dalam dan di Luar Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Sri Warjiyati; Novan Mahendra Pratama; Moh. Haliliyanto (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
This article is about who should have the authority to decide disputes between State Institutions. The 1945 Constitution of the Republic of Indonesia implies the existence of Main State Institutions in the 1945 Constitution of the Republic of Indonesia. Outside of the 1945 Constitution of the Republic of Indonesia, there are various forms and legal basis of Supporting State Institutions. Supporting State Institutions should support the duties of the Main State Institutions so that there is no miss-cooperative. In the 1945 Constitution of the Republic of Indonesia, the Constitutional Court has attribution authority based on Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia and reaffirmed in Article 10 paragraph (1) letters a to d of the Law. Law Number 24 of 2003 concerning the Constitutional Court. Where the Constitutional Court has four powers, one of which is to decide disputes over the authority of state institutions whose authority is granted by the Constitution. The Indonesian nation, which adheres to a presidential system of government, also shows that the President, apart from acting as the Head of Government, can also act as the Head of State. In the case of the Head of State, it is not known what powers the President has. Therefore, this article tries to answer from a different point of view, who has more authority to decide disputes between the Main State Institutions and the Supporting State Institutions.